A Taxonomic study of two species of Thiotricha Meyrick (Lepidoptera: Gelechiidae), from southwestern Japan, with notes on the biology of their immature stages - Kyaw, Khine Mon Mon; Ueda, Tatsuya; Yagi, Sadahisa; Okamoto, Tomoko; Wang, Min; Hirowatari, Toshiya (Zootaxa, 2021)
The taxonomy and biology of the immature stages of two gelechiid species of Thiotricha Meyrick, 1886, found in the southeastern part of the Sino-Japanese region is presented. Thiotricha lumnitzeriella Kyaw, Ueda & Hirowatari sp. nov., from islands in southwestern Japan is described. The larva of this species feeds as a portable case maker on Lumnitzera racemosa Willd. (Combretaceae). Thiotricha gemmulans Meyrick, 1931 originally described from India is newly recorded from Japan, mainland China, and Thailand. This species feeds as a portable case maker on Glochidion zeylanicum var. lanceolatum (Hayata) and G. zeylanicum var. zeylanicum (Gaertn.) A. Juss (Phyllanthaceae). Thiotricha acrophantis Meyrick, 1936 is newly synonymized with T. gemmulans.                Images of the adults of Thiotricha lumnitzeriella sp. nov. and T. gemmulans including genitalia, and images and illustrations of the larval chaetotaxy and pupa for both species are provided. Larval feeding habits are described in detail.